The Counseling Group of Anger Management and Social Skills Training Techniques to Reduce Physical Aggression Behavior - Emansi Saliha, Era Annisa; Eddy Wibowo, Mungin; Awalya, Awalya (Study Program of Guidance and Counseling, Postgraduate Program, Universitas Negeri Semarang, 2021)
Adolescent development aspects that must be attain in overcoming problems are having emotional maturity, intellectuality and awareness of social responsibility so it is not to trigger new conflicts. However, the reality is conflict that often occur in dealing with a problem tend to appear negative behavior, especially physical aggressive behavior. This study aims to examine the effectiveness of group counseling of anger management techniques and social skills training techniques to reduce physical aggression in junior high school students. A total of 21 students were involved in experimental research using randomized pretest posttest comparison group design. The analysis of the results of Wilcoxon and Kruskal Wallis shows that group counseling of anger management techniques, social skills training techniques and a combination of the two techniques are effective in reducing students' physical aggression behavior. Combining anger management and social skills training group counseling techniques are more effective in reducing students' physical aggression behavior compared to the self-management technique group and social skills training. This study recommends the integration of anger management techniques and social skills training techniques to reduce physical aggression in junior high school students.